Supporting family members requested to donate hematopoietic stem cells to a relative: development and pilot testing of a psycho-educational resource. Issue 1 (7th January 2023) - Zomerdijk, Nienke; Turner, Jane; Gottlieb, David; Barnes, Annette; Butler, Jason P.; Markey, Kate A.; Hill, Geoffrey R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Background: In light of the increased demand for related donors in allogeneic stem cell transplantation, recognition of the psychosocial issues has also emerged. While resources supporting unrelated volunteer donors exist, none address the emotional issues specific to being a related donor. Providing related donors with preparatory information could help improve the overall donation experience and donor's outcomes. Objective: The objectives of this study were to develop and pilot test a print-based psycho-educational resource to support donors in coping with the physical and emotional aspects of donating to a relative. This article describes the development and pilot testing of the resource. Methods: Seventeen related donors and eight transplant nurses and physicians (transplant professionals) completed a survey and provided quantitative and qualitative feedback on the acceptability of the resource and preferences regarding the ideal distribution time. Results: Respondents endorsed the resource and found it useful and appropriate for the information needs at different stages of the donation and transplant process. The most useful reported components of the resource were testimonials from previous donors and explanations of blood cancers and the stem cell donation process. Most donor respondents indicated that the resource should be distributed as soon as possible while transplant professionals felt this should be after tissue typing, once the donor is confirmed as suitable. Respondents requested additional information on the side effects of donating and the possibility of being asked to repeat donation if the recipient relapses. More donor testimonials were also desired. Conclusion: The resource appears to be acceptable to donors and transplant professionals and helpful for developing confidence about coping with the physical and emotional aspects of donation. Findings from this study are currently being used to further refine and deliver the resource in additional formats.